2019
DOI: 10.1007/s00259-019-04482-6
|View full text |Cite
|
Sign up to set email alerts
|

[18F]Fluorocholine PET/CT-guided stereotactic body radiotherapy in patients with recurrent oligometastatic prostate cancer

Abstract: Background In the last years, functional imaging has given a significant contribution to the clinical decision-making of biochemically relapsed prostate cancer (PCa). Hereby, we present a prospective study aiming to validate the role of [ 18 F]Fluoro-Methyl Choline ([ 18 F]FMCH) PET/CT in the selection of PCa patients suitable for stereotactic body radiotherapy (SBRT). Methods Patients with biochemical recurrence limited up to three lesions revealed by [ 18 F]FMCH PET/CT were enrolled in the present study and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…A total of 23 articles were selected on the use of PET imaging with [ 68 Ga]PSMA-11 (16 articles/1123 patients) or choline (7 articles/356 patients) for the prediction of radiotherapy response and survival outcomes. Among these studies, 6 articles described the prognostic role of PET after salvage RT ([ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]), while 12 studies assessed the prognostic use of molecular imaging for the treatment of oligometastatic or oligo-recurrent PCa ([ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]). The remaining studies ( n = 5) were variably based on the prognostic evaluation of PET-guided RT in case of localized PCa [ 28 ], newly diagnosed lymph-node-positive PCa [ 29 ], and in a mixed population [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 23 articles were selected on the use of PET imaging with [ 68 Ga]PSMA-11 (16 articles/1123 patients) or choline (7 articles/356 patients) for the prediction of radiotherapy response and survival outcomes. Among these studies, 6 articles described the prognostic role of PET after salvage RT ([ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]), while 12 studies assessed the prognostic use of molecular imaging for the treatment of oligometastatic or oligo-recurrent PCa ([ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]). The remaining studies ( n = 5) were variably based on the prognostic evaluation of PET-guided RT in case of localized PCa [ 28 ], newly diagnosed lymph-node-positive PCa [ 29 ], and in a mixed population [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, PCa patient cohorts are heterogeneous, including only hormone-sensitive patients ([ 21 , 22 , 24 , 27 ]), only castrate-resistant subjects [ 22 ], or both ([ 19 , 20 , 25 ]). Pasqualetti and co-authors [ 16 ], in a group of 46 patients with biochemical recurrence PCa limited up to three lesions, defined the ability of [ 18 F]Choline PET/CT to identify patients suitable for SBRT, resulting in a systemic therapy-free survival of 39.1 months. Additionally, Bouman-Wammes et al [ 17 ] and Kalinauskaite et al [ 19 ] showed that SBRT based on PSMA-PET can reach an excellent local control, with a reduction in the PSA level, minimal toxicity, and long survival.…”
Section: Resultsmentioning
confidence: 99%
“…Another possible treatment strategy is SBRT. There is growing evidence for SBRT in patients with LN metastases coming from trials which evaluated SBRT as metastasis-directed therapy (MDT) in oligometastatic PCa and which included patients with nodal oligometastases [27][28][29][30]. Moreover, there is a retrospective analysis of SBRT in patients with nodal oligorecurrence [31].…”
Section: Discussionmentioning
confidence: 99%
“…Eight of 24 (33%) studies were on choline PET-directed SBRT: one trial [12], one prospective study [13], and six retrospective studies [14][15][16][17][18]. The Surveillance or Metastasis-directed Therapy for Oligometastatic Prostate Cancer Recurrence (STOMP) trial is the first prospective, randomized, phase II trial to assess the potential of MDT, primarily SBRT, to forestall initiation of ADT in men with hormonesensitive metastatic PC with three or fewer detectable extracranial metastases on choline PET [12].…”
Section: Cholinementioning
confidence: 99%